Analysis of Dynamic Plantar Pressure before and after the Occurrence of Neurogenic Intermittent Claudication in Patients with Lumbar Spinal Stenosis: An Observational Study. (2nd July 2020) - Wei, Wei; Xu, Chao; Yang, Xiao-Jiang; Lu, Chang-Bo; Lei, Wei; Zhang, Yang
Abstract : Lumbar spinal stenosis (LSS) is a common disease in the elderly population; it has been reported that patients with LSS have an abnormal gait pattern due to symptom such as neurogenic intermittent claudication (NIC); however, no detailed reports exist on the plantar pressure distributions in LSS patients with NIC. To analysis the plantar pressure characteristics of LSS patients, the Footscan® pressure system was used to perform dynamic plantar pressure measurements in 20 LSS patients (age, 69.5 ± 7.2 years) before and after the occurrence of NIC. The contact time (CT), foot progression angle (FPA), pressure-time integral (PTI), and contact area (CA) were collected and compared between the LSS patients and age-matched healthy subjects in each measurement. The LSS group showed an increase in forefoot CT%, PTI, and CA% in both measurements compared with those in the control group. After the occurrence of NIC in the LSS group, CT%, PTI, and CA% of the forefoot increased further compared with those before the occurrence of NIC. In addition, after the occurrence of NIC, the PTI and CA% of the forefoot shifted from the medial foot to the lateral foot. The results suggested that the plantar pressure distributions of patients with LSS differs from normal subjects due to the posture of waking with lumbar forward flexion, and the forefoot bears a higher relative load. In addition, the occurrence of NIC could affect the plantar pressure distribution of the patients with LSS, predicting the patient's risk of falling to the anterior direction and to the symptomatic side.